3D Computer-vision system for automatically estimating heifer height and body mass. (September 2018) - Nir, Oron; Parmet, Yisrael; Werner, Daniel; Adin, Gaby; Halachmi, Ilan
Abstract : Animal dimensions play a vital role in providing data in support of management decisions regarding livestock. Nevertheless, dairy heifers are still measured manually, a time consuming and stressful task for both the farmer and the animal. This research suggests an approach that utilises a fully automated system to measure a heifer's body. The methodology involves a single low-cost Microsoft Kinect V2 Time-of-Flight 3D sensor, computer vision, machine learning, and object recognition using ellipse fitting with quantile regression as part of the feature extraction phase. The camera was installed at the Volcani Center dairy farm, on the ceiling above a free-walk path between the feeding zone and lying area. Video data of 107 Israeli Holstein heifers were recorded and validated against "gold references" (human-observed body mass, hip height and withers height). The tested system improved the normalised Root Mean Squared Error of estimates over the state of the art models by 70.4%, 69.8% and 42.6% for withers height, hip height, and body mass respectively. The models were also validated on a different dairy farm and yielded similar results. The methodology, may be adapted and applied to other elliptically shaped animal bodies, such as sheep, pigs, horses, and buffalo. Highlights: Dairy heifer body measurement during a free walk via a depth-camera video. A single overhead Kinect v2, 3D camera, used and found accurate and cost-effective. A novel robust feature extraction method was designed and applied. Up to 70% NRMSE improvement on state-of-the-art results. The algorithm was tested and validated on two different herds and farms.